A pyrazolo[1, 5-a]pyridine-fused pyrimidine based novel fluorophore and its bioapplication to probing lipid droplets. Issue 50 (31st May 2016) - Kim, Heejun; Jo, Ala; Ha, Jaeyoung; Lee, Youngjun; Hwang, Yoon Soo; Park, Seung Bum
Abstract : Pyrimidine-containing novel organic fluorophores were discovered and successively applied to monitor the lipid droplets in live cellular systems. Abstract : A new fluorescent core skeleton containing pyrazolo[1, 5- a ]pyridine-fused pyrimidine, called fluoremidine (FD), was discovered. FD analogues were prepared via a one-pot silver-catalyzed cascade cyclization. An N, N -dimethylamino group at the R 1 - and R 2 -positions plays important roles in controlling fluorescence brightness and emission wavelength. An N -acetyl group at the R 3 position contributes to red shifting of the emission wavelength. FD shows excellent solvatochromism with turn-on fluorescence in the lipophilic environment, which was utilized to design a fluorescent probe, FD13, for visualizing lipid droplets in living cells.